RELATIONSHIPS BETWEEN FACTORS INFLUENCING ENGINEERS’ ADHERENCE TO ETHICAL PRACTICES IN ENGINEERING PROFESSION - Sulaiman, Nooraini; Zaharim, Azami; Mastor, Khairul Anwar; Basri, Hassan (Journal of Human Capital Development (JHCD), 2016)
The engineering profession is important due to its significant contribution towards the country’s development, particularly in the aspects of societal development and well-being. However, issues related to ethics and other forms of misconduct among engineers have been highlighted recently. This paper aims to identify the relationships between factors influencing engineers’ adherence to ethical practices in Malaysia. This study was conducted through a research survey involving 376 engineers in various engineering fields, i.e. electrical, mechanical, manufacturing, and civil engineering by using the stratified probability sampling method. Data was analyzed by using descriptive and inferential statistics. The reliability coefficient for each study item, α, was found to be between 0.627 to 0.920. The Pearson correlation analysis showed that there were significant positive relationships between factors influencing engineers’ adherence to ethical practices. The relationship between the discipline at the workplace and environmental factors were found to be the most positive and significant (r= 0.606, p= 0.000). The study findings confirmed that there were significant relationships between factors influencing engineers’ adherence such as inner self conscience, environment, disciplinary regulations at the work place, religion, and experience which are found to be important in influencing engineers’ adherence to ethical practices. It is hoped that this paper can contribute new ideas for academia and policy makers to imbue the appropriate knowledge, religious awareness, and ethical values among engineers in order to uphold the engineering profession. Keywords: works ethics, engineering profession